FAKTOR DETERMINASI LOYALITAS PELANGGAN PT. VERENA MULTI FINANCE Tbk CABANG CIKARANG, BEKASI - Purwanto, Purwanto; Wulandari, Tri (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2024)
This study aims to identify the effect of corporate image, service quality, promotion, and customer satisfaction on customer loyalty of PT Verena Multi Finance Tbk. Quantitative methods were used to analyze data with the help of SmartPLS 3 software. A survey of 311 respondents was selected using random sampling technique. The results of the study showed that company image had no significant effect on satisfaction, while service quality and promotion had a significant effect on satisfaction. Company image and service quality have insignificant influence on loyalty. Promotion and customer satisfaction have a strong influence on loyalty. Customer satisfaction as an intervening variable can fully mediate the effect of service quality on loyalty. Customer satisfaction is not the right mediation for image and promotion in increasing customer loyalty. Corporate image is the lowest factor in an effort to increase customer loyalty, companies need to improve marketing communications, especially in social media related to reputation in the community including product differentiation. Service quality has a great effect on customer satisfaction, so it needs to be maintained in meeting customer expectations through training. Customer satisfaction also has a significant effect that must be maintained.